Report on professional attachment with EM services Pte Ltd. - Ng, Robin Cheng Jiet. (2009)
This report gives a descriptive account of my eight weeks of Professional Attachment from 12th May 1997 to 5th July 1997 with EM Services Pte Ltd. The report will be divided into eight chapters, each focusing on different aspects of the attachment.